Analysis Learning Strategies on Contemporary Advanced Mathematical Thinking - Ayu Aristika (International Conference on Science, Education, and Technology, 2023)
The rapid development of the world of technology also has an impact on world development education so that new and innovative learning models are needed so that students can more quickly understand learning. To answer this situation, we created a learning model that equips students to think critically, creatively and independently through Advanced Mathematics courses using the Contemporary/constructivism model. Utilization of contemporary/constructivism learning models in classroom learning activities has various advantages or benefits. Strength is oriented towards optimal learning activities so that learning objectives can be achieved effectively through the support of lecturers and students in learning. Based on the research results, CTL, Mastery Learning, & Participatory learning strategies have the greatest influence when compared to other learning strategies.